A systematic review of relationship sacrifices from 2002 to 2021: Moving toward inclusivity. Issue 1 (13th October 2022) - Curran, Melissa A.; Young, Valerie J.; Kayabol, Nazlı Büşra Akçabozan; Totenhagen, Casey J.
Abstract: We conducted a systematic review of research on relational sacrifices in romantic relationships from 2002 to 2021 [ N  = 115 studies] to answer three questions: Q1: Whose voices and vantage points are represented in the research?; Q2: What types of questions are valued?; Q3: What are the reflections and connections about relational sacrifices that were learned during the review? To address Q1, we coded sample demographics of study participants on geographical location, race/ethnicity, education/income/SES, gender (i.e., gender differences explored and beyond gender binaries), sexual orientation, age, and disability, using a coding system of 1 (exclusion/absence) to 5 (focus on context‐relevant experiences for underrepresented samples). Results for Q1 showed that the most frequent codes were 1 (exclusion/absence) for information about the samples' disability status, education/income/SES, and both codes for gender (i.e., gender differences explored and beyond gender binaries); when demographic information was reported, the most frequent codes were 2 (compensatory addition) for age, sexual orientation, geographical location, and race/ethnicity. To address Q2, we coded for aspects of the study designs and conceptual dimensions of sacrifice. Results for Q2 showed that a majority of the studies in our review used quantitative and close‐ended measures emphasizing behavioral frequency of sacrifice. For Q3, we include our own reflections and connections about relational sacrifices, questioning research methods, and challenging assumptions drawn from existing research to move toward a more inclusive science.